Agenda setting and coverage of climate change adaptation issues in Kenyan Print Media - Muathe, Carol Wanza; Mogambi, Hezron (Indonesian Journal of Social Sciences, 2025)
This paper analysed leading print media in Kenya, the Daily Nation and the Standard, coverage of the COP 26 and COP 27 major global environment meetings. Using the agenda-setting and social responsibility theory of the press, content analysis examined the frequency and prominence of climate change adaptation in Kenyan print media, stories published a month before, during and after COP 26 and COP 27. The paper analysed stories published in October, November, and December of 2021 and those published in October, November, and December 2022 from the two leading dailies in Kenya. Results show print media in Kenya focuses more on adaptation stories and then mitigation, frame climate change stories using disaster, victims as key actors in disaster stories; government officials feature prominently in events-driven stories. The paper concluded that the agenda-setting role of Kenyan print media impacts public awareness and understanding of climate change adaptation issues. The paper recommends improving on frequency and framing of climate change adaptation stories on community voices, media houses having consistent and prominent placement of climate-related stories, specialised training for local journalists in environmental reporting, and involving experts and policymakers. Diversifying content and public engagement can drive action on climate adaptation.